The benefit of running maintenance habituation before learning of machining process begins - Thomas Sukardi; Bayu Rahmat Setiadi; Afri Yudantoko (Jurnal Pendidikan Vokasi, 2021)
The study was aimed at investigating the advantages of the habituation of running maintenance and supervision over the practice learning process and the learning achievement of the students of Mechanical Engineering Study Program, Faculty of Engineering, Universitas Negeri Yogyakarta. It was participatory classroom action research. The subjects were 80 third-semester students grouped into the group C class. The data on the habituation of running maintenance were collected using a questionnaire; those on the students' learning achievement were collected through documentation and analyzed using a descriptive technique; those on the supervision intensity and machine feasibility were gathered through observations and analyzed using the descriptive qualitative technique. The findings showed that: 1.) The implementation of running maintenance used the systems of coaching, mentoring, and supervision with an optimal intensity of lecturers in teaching-learning machining practices; 2.) The habituation of running maintenance was done through standard procedures, and the implemented action took three cycles; 3.) The achievement of the habituation of running maintenance on students during the implementation of teaching-learning practices was characterized by the rapid job sheet completion that must be taken in one semester; and 4.) With the habituation of running maintenance, the feasibility of the existing machines in the workshop could be maintained.